From Tradition to Transformation: A Case Study on Women Empowerment in Rural India - Dr Rashi (The Bioscan, 2025)
This case study examines Meera Devi a rural woman in India and her transformation from a life dictated by traditional norms to one marked by empowerment and agency. Meera's tale, set against a background of rural women's socioeconomic struggles, demonstrates the enormous influence of grassroots movements and government actions on gender equality. Meera overcomes obstacles such as economic reliance, restricted schooling and medical access, societal norms and a lack of decision-making authority by participating in a Self Help Group (SHG) and gaining access to government programmes. Her path represents a greater trend towards empowerment amongst rural women, aided by efforts that promote financial, educational, medical care, cultural, political, and technical components of empowerment. By exploring Meera's experiences, this case study sheds light on measures for achieving gender equality in rural India, emphasising the need of community participation, campaigning, and ongoing investments in the empowerment of women for inclusive growth.